2022
DOI: 10.1039/d1tc05265a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid crystals based on amino acids and gemini surfactants: tunable phase structure, circularly polarized luminescence and emission color

Abstract: Circularly polarized luminescence (CPL)-active ionic liquid crystalline (ILC) featuring excitation wavelength-dependent (Ex-De) photoluminescence have latent application prospects in display devices. In addition, materials with tunable CPL responses are quite attractive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…As for as we know, excitation-dependent CPL emission is rarely reported in the literature, ,, and the present work reports the first example of excitation-dependent CPL in the polymer system. In addition, the luminescence dissymmetry factor g lum of the core/shell particles is calculated to be 5 × 10 –3 (Figure S11), comparable to the reported nonconventional fluorescent CPL-active materials. …”
supporting
confidence: 72%
“…As for as we know, excitation-dependent CPL emission is rarely reported in the literature, ,, and the present work reports the first example of excitation-dependent CPL in the polymer system. In addition, the luminescence dissymmetry factor g lum of the core/shell particles is calculated to be 5 × 10 –3 (Figure S11), comparable to the reported nonconventional fluorescent CPL-active materials. …”
supporting
confidence: 72%
“…Accordingly, nonconventional luminophores have emerged as promising candidates in the construction of CPL materials. [233][234][235] Wu and colleagues reported the synthesis of bottlebrush poly mers bearing poly(L-lactic acid) (PLLA) or poly(D-lactic acid) (PDLA) side chains on every helical polyisocyanide backbone atom employing grafting-through strategy. [236] The results suggested that the acquired bottlebrush polymers have a degree of polymerization of up to 250 through living polymerization.…”
Section: Nonconventional Fluorescence-based Circularly Polarized Lumi...mentioning
confidence: 99%
“…Accordingly, nonconventional luminophores have emerged as promising candidates in the construction of CPL materials. [ 233–235 ]…”
Section: Newly Emerging Categories Of Polymer‐based Circularly Polari...mentioning
confidence: 99%
“…However, because of the heterogeneity of nonconventional luminogens, pure organic CTE-based CPL materials have rarely been reported. 22,23 Therefore, it is of great significance to design and synthesize new pure organic CTE-based CPL materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared to the conventional luminogens, the CTE luminogens are more hydrophilic, easy to prepare, and biocompatible, making them ideal for green luminescent materials, biological applications, and advanced anticounterfeiting materials. , CTE-based CPL materials have displayed promising abilities in multicolor luminescence, advanced anticounterfeiting materials, and chemical sensing. However, because of the heterogeneity of nonconventional luminogens, pure organic CTE-based CPL materials have rarely been reported. , Therefore, it is of great significance to design and synthesize new pure organic CTE-based CPL materials.…”
Section: Introductionmentioning
confidence: 99%